IPTEKS PENERAPAN FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAERAH PROVINSI SULAWESI UTARA - Rasu, Omega Indria; Pusung, Rudy J. (Universitas Sam Ratulangi, 2018)
The Regional Education Office of North Sulawesi Province is a department engaged in education that carries out services in the field of education from the center to the regions. The way to work in this company is not monotonous. All employees and leaders establish good relationships with each other without reducing respect for their superiors or leaders. This happens because leaders who want to share and socialize with employees. The leaders in the North Sulawesi Provincial Education Office also often provide motivation on various occasions to provide more work enthusiasm for their employees. A good relationship is also proven by the way the opinions are conveyed by employees who are directly discussed by the office leaders. A well-structured organizational system also has an impact on monitoring employee performance because each has responsibilities so that they provide mutual input and encouragement on various occasions. The employees also continue to be provided with training that maximizes each other's performance. A comfortable and safe working atmosphere also makes workers able to work according to their responsibilities. The Regional Education Office of North Sulawesi Province has a mission to serve the community in the field of education so that the employees who are able to provide excellent service also greatly influence the progress of the departmentKeyword: human Resources, performance, employee performance factors